(untitled) (Research, Society and Development, 2022)
Heart failure (HF) is a complication that may be present in patients with type 2 diabetes mellitus associated with increased risks of morbidity and mortality. HF is common and associated with a poor prognosis, despite advances in treatment. The main biological processes that characterize heart failure with preserved ejection fraction are systemic inflammation, accumulation of epicardial adipose tissue, rarefaction of coronary microcirculation, myocardial fibrosis and vascular stiffness. The resulting impairment of left ventricular and aortic distensibility (especially accompanied by impaired glomerular function and sodium retention) causes increased cardiac filling pressures and exertional dyspnea despite relative preservation of left ventricular ejection fraction. Sodium-glucose cotransporter 2 (SGLT2) inhibitors are one of the classes of glucose-lowering therapies that have demonstrated multi-system health benefits. The three inhibitors that are used are: empaglifozin, canaglifozin and dapagliflozin. Empaglifozin reduced the risk of pump failure and sudden death, the two most common modes in patients with heart failure. Regardless of their actions on blood glucose, SGLT2 inhibitors exert a wide range of biological effects including actions to inhibit cardiac inflammation and fibrosis, antagonize sodium retention, and improve glomerular function that may ameliorate the pathophysiological disorders of heart failure.